Preoperative nutritional status assessment predicts postoperative outcomes in patients with surgically resected non-small cell lung cancer. Issue 9 (September 2018) - Ramos, Ricard; Nadal, Ernest; Peiró, Inma; Masuet-Aumatell, Cristina; Macia, Ivan; Rivas, Francisco; Rosado, Gabriela; Rodriguez, Pau; Ureña, Anna; Padrones, Susana; Aso, Samantha; Deniz, Carlos; et al.
Abstract: Background: As nutritional status plays an important role in outcomes after surgery, this study evaluated the association between preoperative nutritional status (NS) and postoperative outcomes after major resection for lung cancer. Methods: We identified 219 patients with a diagnosis of cancer who underwent pulmonary resection from 2010 to 2012. Preoperative NS was assessed by anthropometric and biological parameters, body mass index (BMI), and the Nutritional Risk Index (NRI). We stratified this population into 4 BMI groups: underweight, normal weight, overweight and obese and 4 NRI groups: well-nourished ; mildly malnourished ; moderately malnourished and severely malnourished . The outcomes measured were postoperative complications; 30-day postoperative mortality; hospital length of stay (LOS), overall survival (OS) and disease-free survival (DFS). We performed both unadjusted analysis and adjusted multivariable analysis, controlling for statistically significant variables. Results: Mean BMI and NRI were, respectively, 26.5 ± 4.3 and 112.4 ± 3.3. There were no significant differences between BMI categories and resection type, pathological stage, or overall postoperative complications. By contrast, significant differences (p < 0.05) in postoperative complications were observed among the NRI groups. LOS was longer in underweight and/or malnourished patients. In terms of OS, we found no significant differences according to NRI and BMI; however, patients with underweight had significantly shorter DFS compared with patients with overweight and obesity (log-rank p-value = 0.001). Conclusion: NS as measured by the NRI is an independent predictor of the risk of postsurgical complications, regardless of clinicopathologic characteristics. NRI might therefore be an useful tool for identifying early-stage lung cancer patients at risk for postoperative complications.